2019
DOI: 10.1097/md.0000000000014502
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a home health care program for disabled patients in Taiwan

Abstract: The aim of this study was to evaluate the impact of home health care (HHC) for disabled patients. We conducted a nationwide population-based retrospective cohort study. A total of 5838 disabled patients with HHC were identified to match by propensity score with 15,829 disabled patients without HHC receiving tube or catheter care (tracheostomy tube, nasogastric tube, urinary catheter, cystostomy tube, nephrostomy tube) or stage 3 or 4 pressure sore care from the Taiwanese National Health Insurance Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 22 publications
1
14
1
Order By: Relevance
“…The present study demonstrates the pattern of medical care needs in HHC in Taiwan at a national level during 1997 and 2013, which is unique compared to previous studies investigated in a shorter period [8][9][10][11][12]. We found that women with income-dependent status had the highest burden of medical care needs in HHC recipients in Taiwan.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…The present study demonstrates the pattern of medical care needs in HHC in Taiwan at a national level during 1997 and 2013, which is unique compared to previous studies investigated in a shorter period [8][9][10][11][12]. We found that women with income-dependent status had the highest burden of medical care needs in HHC recipients in Taiwan.…”
Section: Discussionsupporting
confidence: 59%
“…Despite several medical and social elucidations that have been articulated in attempts to account for the differences in medical care needs for HHC, how gender and income influence this association remains unclear, especially for the older population [ 10 , 12 ]. In our study, an increasing proportion of women was noted in the groups with higher medical care needs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The slightly higher risk of ET in the HHC group compared to those who did not have HHC may have occurred because people who received HHC may have had more multi-morbidities, more complex care needs, or have been at increased risk of using acute healthcare services before the HHC service [ 30 , 31 ]. For example, disabled people who received HHC in Taiwan had a higher risk of hospitalisation or ER transition after HHC (OR = 1.6, 95 % CI 1.41–1.83 and OR = 1.16, 95 % CI: 1.04–1.30, respectively) compared to the non-HHC group, even though HHC reduced hospital admissions by 80% and ER visits by 65% for people in the HHC group within the year after HHC service [ 30 ]. Another explanation is that better care coordination in home-based services compared with the usual care may identify more cases with unmet needs, leading to an increase in admissions for elderly people [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%